TWO FACES OF PARTICIPATION: THE STORY OF KERALA - PATRICIA JUSTINO (PRUS WORKING PAPER NO. 19, 2003)
This paper analysis the impact of collective action and political participation on the economic development of the south Indian state of Kerala over the last three decades. Despite its low economic basis, Kerala's successive governments have implemented a large redistributive programme that resulted in impressive levels of social development. Kerala's success has been largely attributed to the actions of organised collective movements, both in the formal and informal sectors, in the form of militant peasants associations and labour unions. Collective actions have, however, also contributed towards political instability, increase in the risk of investment and uncertainty in labour productivity. This paper examines the effects of collective actions on Kerala's economic growth during the last three decades using time-series analysis techniques, considering in turn collective action and redistributive policies to be external and then endogenous variables to the process of economic growth in Kerala. The results show that while some forms of collective action can contribute towards the decrease of poverty and increase in state income, other forms harm economic growth. We compare these results with those obtained for a panel of 14 major Indian states.